Ketamine in the Treatment of Obsessive-Compulsive Disorder: A Systematic Review. Issue 2 (March 2022) - Bandeira, Igor D.; Lins-Silva, Daniel H.; Cavenaghi, Vitor Breseghello; Dorea-Bandeira, Ingrid; Faria-Guimarães, Daniela; Barouh, Judah L.; Jesus-Nunes, Ana Paula; Beanes, Graziele; Souza, Lucca S.; Leal, Gustavo C.; Sanacora, Gerard; Miguel, Euripedes C.; et al.
Abstract: Introduction: First-line treatment for obsessive-compulsive disorder (OCD) includes exposure and response prevention behavioral therapy and serotonin reuptake inhibitors, particularly in combination. New and more effective treatments are needed, give that recent studies suggest that glutamatergic neurotransmission contributes to the pathophysiology of the disorder. In these circumstances, ketamine, as a potent N-methyl-D-aspartate receptor antagonist and glutamate modulator, offers alternative possibilities for OCD treatment. Methods: This systematic review aims to investigate the effects of ketamine in OCD, following the Preferred Reporting Items for Systematic Review and Meta-analyses Protocols (PRISMA-P). Searches were carried out using the PubMed/MEDLINE, Embase, and PsycINFO databases. Results: Nine articles were included, of which three were randomized controlled trials, three case reports, two open-label trials, and one a retrospective chart review. Reported data have shown a potential for fast onset of action and good tolerability of ketamine for OCD, even though the principal studies used only single-session racemic ketamine treatments, administered intravenously, and the results have been erratic. In addition, none of the available evidence demonstrates whether racemic ketamine, S-ketamine, or R-ketamine has the best efficacy in controlling OCD symptoms, and only sparse evidence suggests that a combination of ketamine and psychotherapy could benefit patients with OCD. Conclusion: In order to advance clinical practice regarding the use of ketamine in treating OCD, future randomized, double-blind, placebo-controlled trials are required. These trials need to use larger samples to explore ketamine and its enantiomers, with different methods of administration, multiple sessions, and appropriate washout periods.